(3x - 1)^100 = 1024^10
K
Khách
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Những câu hỏi liên quan
HX
2
QK
18 tháng 11 2015
(3x-1)^100=1024^10
(3x-1)^100 = (2^10)^10
(3x-1)^100 = 2^100
3x-1=2
3x=3
x=1
XC
0
NT
0
TP
1
7 tháng 12 2015
10(x-20)=10
x - 20 = 10-10
x - 20 = 0
x = 0 + 20
x = 20
597 - 3x = 9.2
597 -3x = 18
3x = 597 - 18
3x = 579
x = 579 : 3
x = 193
10 + 2x = 1024 : 64
10 + 2x = 16
2x = 16 - 10
2x = 6
x = 6 : 2
x = 3
N
3
11 tháng 10 2020
102410 = (210)10 = 2100
Vì 2100 < 10100 nên 102410 < 10100
E
0
(3x - 1)^100 = 1024^10
(3x-1)^100=(2^10)^10
(3x-1)^100=2^100
=> 3x-1=2
=> 3x =2+1
=> 3x =3
=> x =3:3
=> x =1